Instanton counting and O-vertex - Nawata, Satoshi; Zhu, Rui-Dong (The journal of high energy physics, 2021)
A bstract We present closed-form expressions of unrefined instanton partition functions for gauge groups of type BCD as sums over Young diagrams. For SO( n ) gauge groups, we provide a fivebrane web picture of our formula based on the vertex-operator formalism of the topological vertex with a new type called O-vertex for an O5-plane.